Comparison of different gene-therapy methods to treat Leber hereditary optic neuropathy in a mouse model - Velmurugan, Sindhu; Chou, Tsung-Han; Eastwood, Jeremy D.; Porciatti, Vittorio; Liu, Yuan; Hauswirth, William W.; Guy, John; Yu, Hong (Frontiers in Neuroscience, 2023)
Introduction Therapies for Leber hereditary optic neuropathy (LHON), in common with all disorders caused by mutated mitochondrial DNA, are inadequate. We have developed two gene therapy strategies for the disease: mitochondrial-targeted and allotopic expressed and compared them in a mouse model of LHON. Methods A LHON mouse model was generated by intravitreal injection of a mitochondrialtargeted Adeno-associated virus (AAV) carrying mutant human NADH dehydrogenase 4 gene (hND4/m.11778G>A) to induce retinal ganglion cell (RGC) degeneration and axon loss, the hallmark of the human disease. We then attempted to rescue those mice using a second intravitreal injection of either mitochondrial-targeted or allotopic expressed wildtype human ND4. The rescue of RGCs and their axons were assessed using serial pattern electroretinogram (PERG) and transmission electron microscopy. Results Compared to non-rescued LHON controls where PERG amplitude was much reduced, both strategies significantly preserved PERG amplitude over 15 months. However, the rescue effect was more marked with mitochondrial-targeted therapy than with allotopic therapy (p = 0.0128). Post-mortem analysis showed that mitochondrial-targeted human ND4 better preserved small axons that are preferentially lost in human LHON. Conclusions These results in a pre-clinical mouse model of LHON suggest that mitochondrially-targeted AAV gene therapy, compared to allotopic AAV gene therapy, is more efficient in rescuing the LHON phenotype.